Fermi-level-driven interfacial charge redistribution for stable alkaline seawater oxidation at the ampere level - Dongjian Kang; Yi Zhang; Zizai Ma; Hongming Jiao; Shumin Wang; Hongfei Xu; Yanmin Lu; Yihan Zhao; Jiaxi Wang; Xuekun Liu; Xiaoguang Wang (Chemical Engineering Journal, 2026)

Decoding divergent degradation in single-phase 3R-AB4 and 2H-A5B19 superlattice hydrides for ultra-stable hydrogen storage - Hang Lu; Lixiang Ma; Kuiyue Wang; Qiuyue Jia; Lu Zhang; Yuan Li; Qiuming Peng; Shumin Han (Chemical Engineering Journal, 2026)

Anemoside B4 upregulates DDAH2 and attenuates oxidative stress induced endothelial dysfunction - Shuxian Lu; Yao Yi; Qin Chen; Luling He; Margaret Baldini; Dan Shan; Limin Gong; Liang Qiu; Shumin Ma; Manman Qin; Yanyun Fang; Yifeng Zhang; et al. (Molecular and Cellular Biochemistry, 2026)

Infant-derived bifidobacterium can enhance the ability to respond to influenza virus infection by promoting type I interferon-mediated immunity - Jiaqian Shentu; Qinggang Xie; Minghui Yan; Shumin Wang; Xiaoxuan Sun; Chengcheng Zhang; Peijun Tian; Xiaomei Lv; Bo Yang; Wenwei Lu; Shumao Cui; Gang Wang; et al. (Food Bioscience, 2026)

Immune‐Inflammatory Imbalance in Mice Under High Humidity and Three Different Ambient Temperatures: Insights From Gut Microbiome and Serum Metabolomics - Hua Yang; Shumin Wei; Xiaomin Ou; Wei Jiang; Weihui Lu; Taohua Lan (Environmental Microbiology, 2026)
Gut microbiota and metabolites have been increasingly implicated in the pathogenesis of immune inflammation, which may be affected by environmental factors. This study aimed to explore the influence of co‐exposure to high humidity and temperatures (low, normal or high) on biomarkers of immune inflammation and potential mechanisms. We established C57BL/6J mice models (with equal numbers of males and females) of high humidity and low temperature (HH‐LT), normal temperature (HH‐NT) or high temperature (HH‐HT) co‐exposure environments to observe the impact of high humidity and different temperature co‐exposure environments for 28 and 56 consecutive days. Following exposure, results showed that all six combined exposure conditions significantly increased pro‐inflammatory cytokines (TNF‐α, IL‐1β, IL‐12p70), decreased anti‐inflammatory cytokines (IL‐4, IL‐10) and elevated the Teff/Treg ratio in the spleen. Gut microbiota analysis revealed reduced Akkermansia and increased Desulfovibrio and Enterorhabdus . Serum metabolomics identified widespread disturbances enriched in pathways including protein digestion and absorption, lysine degradation, phenylalanine metabolism and unsaturated fatty acid biosynthesis. Pearson correlation analysis confirmed significant associations among microbial shifts, immune‐inflammatory dysregulation and metabolic perturbations—suggesting that high humidity combined with different temperatures correlated with immune imbalance, likely mediated by gut dysbiosis and serum metabolic disruption.

Effects of photochemical and aqueous-phase oxidation on secondary formation during the 31st FISU Summer World University Games, 2023 - Xiaoling Zeng; Zhier Bao; Jiawei Zhou; Guangming Shi; Li Zhou; Shumin Zhang; Xin Qi; Keding Lu; Chongzhi Zhai; Zhenliang Li; Xin Li; Chao Peng; et al. (Journal of Environmental Sciences, 2026)

Fine-mapping and candidate gene analysis of qFF3.1 conferring fruit firmness in a modern tomato variety - Yunhao Han; Xin Li; Can Zhu; Yonglian Wang; Junling Hu; Shumin He; Saifeng Guo; Xiaoxiao Lu; Chunyang Pan; Zejun Huang; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2026)

Biodegradation of 2,4-di-tert-butylphenol in continuous cropping field: Impacts on sustainable cultivation of Lilium brownii - Shumin Zhong; Longzhu Tang; Lu Su; Deyuan Chen; Xuwei Li; Li Shi; Xiaogang Li; Xiaolan Liao (Journal of Environmental Management, 2026)

The role of transition metal Y, Ti, and Zr substitutions on the hydrogen storage of Ce2Ni7-type Sm–Mg–Ni-based superlattice alloys - Lian Cong; Zhuohan Zhang; Kuiyue Wang; Yuan Li; Qiuming Peng; Lu Zhang; Shumin Han (Chemical Engineering Journal, 2026)

The immunosuppressive receptor FcγRIIb (CD32b) gets involved in immune response of Nile Tilapia (Oreochromis niloticus) against bacterial infection - Jiadong Li; Shumin Du; Qingliang Zeng; Zhanyao Lin; Yansong Wang; Lu Deng; Xiaoxue Yin; Yanjian Yang; Zheng Guo; LiangLiang Mu; Jianmin Ye (Aquaculture, 2026)

Study on the Mechanism of Acanthopanax senticosus Extract Intervening in the Regulation of Parkinson’s Disease by BV2 Microglial Cell–Derived Exosomes - Ningxia Lu; Yehao Wang; Yi Lu; Fang Lu; Shumin Liu (Molecular Neurobiology, 2026)

Dual-functional Nb/Sm3H7 interface for enhanced hydrogen storage performance in Mg/MgH2 system - Zhuohan Zhang; Zhichao Yu; Zhaoyang Liu; Lixiang Ma; Jing Wang; Yuan Li; Lu Zhang; Shumin Han (Chemical Engineering Journal, 2025)

Potential new drug sources for the treatment of Parkinson’s disease: flavonoid O-glycosides - Yehao Wang; Jinjin Yang; Xin Jiang; Runda Yuan; Ruyang Cheng; Ningxia Lu; Ao Gao; Shumin Liu (Molecular Biology Reports, 2025)

Spatial metabolomics reveals the effects of Acanthopanax senticosus on region-specific alterations in neurotransmitters and metabolites levels in the brains of α-syn transgenic Parkinson’s disease model mice - Qi Zheng; Yi Lu; Donghua Yu; Liangyou Zhao; Yu Wang; Pingping Chen; Fang Lu; Shumin Liu (Metabolic Brain Disease, 2025)

Unveiling the intrinsic electrochemical properties and stability of phase-pure A5B19 La–Mg–Ni-based superlattice allotropes - Kuiyue Wang; Anyi Zhang; Ning Zhang; Wenfeng Wang; Shumin Han; Qiuming Peng; Yuan Li; Lu Zhang (Chemical Engineering Journal, 2025)

Unlocking novel angiotensin-converting enzyme inhibitory peptides from Nili Ravi buffalo milk β-casein: A synergistic strategy combining targeted hydrolysis, 3D-QSAR modeling, and mechanistic insights - Jionghui Gu; Shumin Yue; Xin Yang; Zuyi Lu; Zhaorui Wang; Xuechun Wei; Liqin Zhou; Zhenxia Zhao; Zhongfeng Shi; Zhongxing Zhao (Food Bioscience, 2025)

High-capacity superlattice La0.55Sm0.20Mg0.25Ni3.27Al0.01 hydrogen storage alloys with series of (A7B23) -(A2B7)1- (x = 0, 0.1, 0.9) structures for nickel-metal hydride batteries - Ning Zhang; Beichen Zhao; Wenfeng Wang; Anyi Zhang; Qiuyue Jia; Yuan Li; Lu Jian; Tianzi Li; Shumin Han; Lu Zhang (Chemical Engineering Journal, 2025)

Hierarchical Al-CoP/Ni2P heterostructure for alkaline hydrogen evolution reaction - Kangli Chen; Zhichao Yu; Yuan Li; Wenfeng Wang; Lu Zhang; Shumin Han (Fuel, 2025)

Biomimetic nanozyme outperforms natural counterpart: Unlocking novel CO2 sequestration potential - Shumin Ni; Weifeng Lyu; Zemin Ji; Lu Wang; Mingyuan Wang; Chang He; Kai Wang; Yue Guan; Keqiang Wei; Xiuxiu Pan (Journal of Cleaner Production, 2025)

Expression of allergenic protein and polycyclic aromatic hydrocarbons in the Platanus pollen grains collected from different area of Shanghai - Lu Senlin; Zhang Lu; Liu Jin; Zhou Shumin; Zhang Wei; Shinichi Yonemoch; Liu Xinchun; Lin Yichun; Enyoh Christian Ebere; Wang Weiqian; Wang Qingyue (Aerobiologia, 2025)

Identification of the effects of low temperature on grain-setting rate of different types of late-season rice (Oryza sativa) during heading - Yibo Gao; Yi Li; Ling Huang; Jinsong Zhao; Shumin Li; Jianxin Lu; Xinghua Li; Tewu Yang (Field Crops Research, 2024)

Arsenic sulfide enhances radiosensitivity in rhabdomyosarcoma via activating NFATc3-RAG1 mediated DNA double strand break (DSB) - Yu Cai; Chuanying Zhu; Shumin Lu; Ting Kang; Shuxian Chen; Zhuowei Feng; Siyu Chen (Chemico-Biological Interactions, 2024)

Enhanced denitrification performance of electrotrophic bio-cathode mediated by biochar and potential microbial mechanism - Meizhen Tang; Fei Lu; Zhina Guo; Shumin Yao; Shiqiang Ma; Yuewei Yang (Journal of Water Process Engineering, 2024)

Crucial role of Mg on phase transformation and stability of Sm–Mg–Ni-based AB2 type hydrogen storage alloy - Yongxi Zhang; Yuan Li; Guanjiu Wu; Chenfeng Fan; Lu Zhang; Shumin Han (Chemical Engineering Journal, 2023)

Revealing the crucial role of Carbon-Centered radicals in UV/PAA process for trace amounts of organic contaminants removal - Yuanxi Huang; Lu Luo; Shumin Zhu; Kai Yin; Lingjun Bu; Shiqing Zhou (Chemical Engineering Journal, 2023)

Comparison of the heterogeneous reaction of NO2 on the surface of clay minerals and desert dust particles - Teng Ma; Jingying Niuhe; Senlin Lu; Lu Zhang; Shumin Zhou; Jin Liu; Wei Zhang; Xinchun Liu; Enyoh Christian Ebere; Qingyue Wang; Weiqian Wang (Environmental Pollution, 2023)

Catalytic effect of bamboo-like carbon nanotubes loaded with NiFe nanoparticles on hydrogen storage properties of MgH2 - Yaokun Fu; Zhichao Yu; Sanyang Guo; Yuan Li; Qiuming Peng; Lu Zhang; Shikui Wu; Shumin Han (Chemical Engineering Journal, 2023)

A long-life aqueous Zn battery enabled by simultaneous suppressing cathode dissolution and Zn dendrites via a novel water-in-deep eutectic solvent electrolyte - Wenfeng Wang; Ruyue Li; Zeang Duan; Jiajin Zhao; Yadi Qi; Qiubo Guo; Qiuming Peng; Desong Wang; Shumin Han; Lu Zhang (Chemical Engineering Journal, 2023)

New insight into the co-adsorption of oxytetracycline and Pb(II) using magnetic metal–organic frameworks composites in aqueous environment: co-adsorption mechanisms and application potentials - Meng-lu Wang; Zhe Zhao; Shumin Lin; Ming Su; Bolong Liang; Shu-xuan Liang (Environmental Science and Pollution Research, 2022)

Comparison of the characterization of allergenic protein 3 (Pla a3) released from Platanus pollen grains collected in Shanghai during the spring of 2019 and 2020 - Xingzi Wang; Shumin Zhou; Senlin Lu; Lu Zhang; Teng Ma; Xinchun Liu; Wei Zhang; Shuijun Li; Kai Xiao; Weqian Wang; Qingyue Wang (Aerobiologia, 2022)

MaMPK2 enhances MabZIP93-mediated transcriptional activation of cell wall modifying genes during banana fruit ripening - Chaojie Wu; Wei Shan; Shumin Liang; Lisha Zhu; Yufan Guo; Jianye Chen; Wangjin Lu; Qianfeng Li; Xinguo Su; Jianfei Kuang (Plant Molecular Biology, 2019)

A Critical Time-Window for the Selective Induction of Hippocampal Memory Consolidation by a Brief Episode of Slow-Wave Sleep - Yi Lu; Zheng-Gang Zhu; Qing-Qing Ma; Yun-Ting Su; Yong Han; Xiaodong Wang; Shumin Duan; Yan-Qin Yu (Neuroscience Bulletin, 2018)

Dietary Supplementation with Chromium Picolinate Influences Serum Glucose and Immune Response of Brown-Egg Laying Hens - Shumin Zhang; Xiaoming Sun; Xiudong Liao; Lin Lu; Liyang Zhang; Qiugang Ma; Xugang Luo (Biological Trace Element Research, 2018)

Variations in High-frequency Oscillations of Tropical Cyclones over the Western North Pacific - Shumin Chen; Weibiao Li; Zhiping Wen; Mingsen Zhou; Youyu Lu; Yu-Kun Qian; Haoya Liu; Rong Fang (Advances in Atmospheric Sciences, 2018)

Insecticide resistance status and detoxification enzymes of wheat aphids Sitobion avenae and Rhopalosiphum padi - Liuping Zhang; Hong Lu; Kun Guo; Shumin Yao; Feng Cui (Science China Life Sciences, 2017)

Spy1 participates in the proliferation and apoptosis of epithelial ovarian cancer - Shumin Lu; Rong Liu; Min Su; Yingze Wei; Shuyun Yang; Song He; Xia Wang; Fulin Qiang; Chen Chen; Shuyang Zhao; Weiwei Zhang; Pan Xu; et al. (Journal of Molecular Histology, 2016)

Basin modelling of gas migration and accumulation in volcanic reservoirs in the Xujiaweizi Fault-depression, Songliao Basin - Wenguang Wang; Min Wang; Shuangfang Lu; Shumin Chen; Min Zheng; Xiaozhi Wu (Arabian Journal of Geosciences, 2016)

Identification and analysis of high-frequency oscillations in the eyewalls of tropical cyclones - Shumin Chen; Youyu Lu; Weibiao Li; Zhiping Wen (Advances in Atmospheric Sciences, 2015)

Expression and clinical role of TCTP in epithelial ovarian cancer - Chen Chen; Yan Deng; Minhui Hua; Qinghua Xi; Rong Liu; Shuyun Yang; Jian Liu; Jianxin Zhong; Meilan Tang; Shumin Lu; Zhimei Zhang; Xiao Min; et al. (Journal of Molecular Histology, 2015)

Thermal effect of intrusive rock on hydrocarbon generation from organic matter - Min Wang; Shuangfang Lu; Shumin Chen; Jianzhong Li; Haitao Xue; Xiaozhi WU; Guohui Chen; Man Zheng; Shiguang Zhang; Wenbiao Huang (Arabian Journal of Geosciences, 2015)

Enhanced expression of PCV2 capsid protein in Escherichia coli and Lactococcus lactis by codon optimization - Wentao Kong; Jian Kong; Shumin Hu; Wenwei Lu; Ke Wang; Mingjie Ji (World Journal of Microbiology and Biotechnology, 2011)

Xi River virus, a new bat reovirus isolated in southern China - Linfeng Du; Zongji Lu; Yu Fan; Keyin Meng; Yu Jiang; Yan Zhu; Shumin Wang; Wanjun Gu; Xiaohuan Zou; Changchun Tu (Archives of Virology, 2010)

Spatiotemporal evolution of urban land uses in modern urbanization of China - Shumin Zhang; Baolei Zhang; Lei Zhang; Chunxia Lu; Xiaoling Cheng (Chinese Geographical Science, 2010)